Recent Status of Prevalence of Rodents Infestation in Baghdad City - Kadhim, A.H. H.; Mahdi, H.Q. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was carried out for  the period    March 2007 -January 2008 , in order to describe the status of the environmental sanitation and the prevalence of rodents infestation in nine quarters in Baghdad city . The results showed that the PI varied between 40 -100% in garbage accumulation places and between 33.3 - 100% in theother sites (houses , shops , bakeries and book shops) . It was noticed that, no rodents control activities were carried out from 2003 till now because of the unsuitable conditions a especially in Baghdad city . The level of ES was bad in general according to three degrees of evaluation (weak , mid and good)